Comparative characteristics of tubular furnaces with injection and acoustic burners - D. B. Vafin; A. V. Sadykov; M. A. Butyakov (Известия высших учебных заведений: Проблемы энергетики)
Showing comparative thermal and aerodynamic characteristics of technological tubular furnaces with injection burners located on the roof of the chamber and the acoustic radiation burner flame grazing arranged in one layer on the side wall. Isotherm shown in the amount of radiation chamber, view lines of the stream function, the distribution of molar concentrations of radiating components of the combustion products and graphs of the surface heat flux density along the length of the reaction tubes. The results obtained by numerically solving the system of equations of two-dimensional radiative transfer in S2 - approximation of the discrete ordinate method, the energy of the turbulent motion of the combustion products, k - e turbulence model and a simple model of the combustion of gaseous fuels.